2011
DOI: 10.1007/s10464-011-9479-1
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Process Analysis of Mother–Child Emotional Relationships in a Rural Appalachian European American Community

Abstract: This prospective longitudinal study examines emotional relationships in 58 Appalachian mother-child dyads observed at home at 5 and 20 months. Between infancy and toddlerhood, 3 of 4 dimensions of dyadic emotional relationships were stable, and 3 remained continuous in their mean level. Increasing maternal age was associated with greater maternal sensitivity and structuring and with more responsive and involving children. Marital status and father presence in the home as well as maternal openness, parenting kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…For South Korean mothers, only written materials appeared to be a useful source of parenting knowledge. Finally, for U.S. mothers, age, education, and occupation as well as perceived parenting supports from written materials were associated with their parenting knowledge (notably, among U.S. mothers, mothers’ mothers, fathers’ mothers, and other relatives were reported as negatively associated with parenting knowledge; see also Bornstein, Putnick, & Suwalsky, 2012). Although we included sociodemographic and support variables in an effort to understand differential societal patterns of parenting knowledge, we did not plumb cultural belief systems or analyze the specific items on which mothers in different societies scored differently.…”
Section: Discussionmentioning
confidence: 91%
“…For South Korean mothers, only written materials appeared to be a useful source of parenting knowledge. Finally, for U.S. mothers, age, education, and occupation as well as perceived parenting supports from written materials were associated with their parenting knowledge (notably, among U.S. mothers, mothers’ mothers, fathers’ mothers, and other relatives were reported as negatively associated with parenting knowledge; see also Bornstein, Putnick, & Suwalsky, 2012). Although we included sociodemographic and support variables in an effort to understand differential societal patterns of parenting knowledge, we did not plumb cultural belief systems or analyze the specific items on which mothers in different societies scored differently.…”
Section: Discussionmentioning
confidence: 91%
“…The general state of knowledge that parents possess constitutes a frame of reference from which they interpret their children's behaviors. More knowledgeable parents have more realistic expectations of their children, they are more likely to behave in developmentally appropriate ways with their children (Grusec & Goodnow, 1994), and knowledge of child-rearing and child development explains variation in mother's emotional relationships with their children (Bornstein, Putnick, & Suwalsky, 2012).…”
Section: This Studymentioning
confidence: 99%
“…Parenting satisfaction refers to the perceptions of pleasure and gratification arising from the parenting role. Satisfaction affords a sense of well-being to parenting that translates to positive emotional availability to children in parent–child interactions (Bornstein et al, 2012); thus, parenting satisfaction is intimately tied to parental affective reactions to their children. Parenting satisfaction is consequential because early parental caregiving patterns often persist and influence the ways in which parents interact with their children over time (Holden & Miller, 1999).…”
Section: This Studymentioning
confidence: 99%
“…Central to human development is emotional growth, depending upon the reciprocal interpretation of cues between primary caregiver and infant (Bornstein et al, 2012). In determining how parents gather and use knowledge of their infants mental health, we found that researchers focused on how the dyadic relationship between primary caregiver (usually the mother) and infant shapes the regulation of one’s own emotions and subsequent social relationships with others (Lewis, 2005).…”
Section: Resultsmentioning
confidence: 99%